The Relationship between Myocardial Strain Using 2D Speckle Tracking Echocardiography and Coronary Lesion Severity Measured by Syntax Score in Patients with Chronic Coronary Syndrome at Haji Adam Malik Hospital - Purba, Antonius Leonardo; Akbar, Nizam Zikri; Sarastri, Yuke (Journal of Society Medicine, 2024)
Introduction: Coronary heart disease continues to be the leading cause of morbidity and death worldwide. The cardiac dysfunction known as chronic coronary syndrome is caused by atherosclerosis-related obstruction or constriction of coronary arteries. Currently, One interesting non-invasive technique is GLS assessment, which has shown to be useful in predicting coronary lesions in chronic coronary syndrome patients. This study aims to evaluated the correlation between myocardial strain based on 2-D Speckle-Tracking Echocardiography and the severity of coronary lesions in chronic coronary syndrome patients at Haji Adam Malik Hospital Medan Method: This research is an analytical observational study with a cross sectional design on patients who diagnosed with chronic coronary syndrome and treated at H Adam Malik General Hospital Medan which met the inclusion and exclusion criteria. Sampling was carried out starting in January to December 2023. In bivariate analysis, the Fisher Exact test is used if the data is not normally distributed, and the chi square test is used if the data is normally distributed. P values less than 0.05 indicate statistical significance in data analysis using computer statistical methods. Results: Myocardial global longitudinal strain (GLS) based on 2-D Speckle-Tracking Echocardiography was significantly associated with the severity of coronary lesions as measured by syntax score in chronic coronary syndrome patients (p value  0.0001, OR 2.732, 95% CI 1, 81-4,11). As a predictor of coronary lesions severity based on the Syntax score in patients with chronic coronary syndrome, the global longitudinal strain (GLS) cut-off value of -17.37 demonstrates a sensitivity of 92.9% and a specificity of 83.6%. Conclusion: Myocardial global longitudinal strain (GLS) with a cut-off value of -17.37 can be used as a predictor coronary lesions severity in chronic coronary syndrome patients with a sensitivity of 92.9% and a specificity of 83.6%.